Significance of the early rehabilitation in lumbar sindrome - Lazarevska S.; Gontarev S.; Aleksovska Velichkovska L.; Shukova Stojmanovska D. (Faculty of physical education, sport and health, 2019)
Introduction: Disability associated with chronic lumbar pain is one of the most common painful states of the modern human being and represents a benign condition with highest costs in the healthcare system. Objective: To detect the differences between the results from the treatment of patients with low lumbar pain, depending on the type of the applied methods of treatment: physical therapy or medical treatment. Materials and methods: This study has enrolled 200 patients with low lumbar pain, treated with medical and physical therapy that, according to the given therapy, were divided into two groups and examined before and after completion of the treatment. Oswestry Index was used for assessment of disability associated with lumbar pain. Results: The respondents were with an average age of 53.8 years, most of who were female patients (62 %) and had normal body weight, (BMI=22.6). 34% of the respondents had a job position that mostly involves seating, whilst 48% of them had a job which does not require physical activity. T-test indicated nearly two times bigger drop of the disability index in patients who had received physical therapy (28.8) in comparison with the drop of the disability index in patients who had received medical therapy (15.72), (p<0.05). Conclusion: The early practice of physical therapy and reduction of the longer period spent for resting bring better and quicker results for reduction of the disability associated with lumbar pain.
Keywords: low lumbar pain, disability, deformity, kinesitherapy, ergonomic principles